Monitoring of Milk Quality With Disposable Taste Sensor. - Yap, Maxsim Mee Sim; Shya, T.J.; Ahmad, M.N.; Shakaff, A.Y.; Othman, Prof.Madya Abdul Rahman; Hitam, M.S. (2003)
A disposable screen-printed multi channel taste sensor composed of several types of lipid as transducers and a computer as data analyzer could detect taste in a manner similar to human gustatory sensation.